DAMPAK KENAIKAN HARGA PUPUK NON SUBSIDI TERHADAP EKONOMI PETANI SAYUR DI DESA BARUH BUKIT - Jetli Satrio (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research is based on the very increasing price of non-subsidized fertilizers and the lack of subsidized fertilizers in rural areas, this study aims to see how much the increase in the price of non-subsidized fertilizers and how big the impact on the economy of vegetable farmers in Baruh Bukit village, this type of qualitative descriptive research by conducting interviews with several vegetable farmers and then processing and analyzing the data, it was found that the increase in the price of non-subsidized fertilizers in Baruh Bukit Village experienced a significant increase and had a fairly bad impact on the economy of farmers in Baruh Bukit Village and the situation was exacerbated by the selling price of crops is cheap in the market, while the necessities of life continue to increase.